American poetry: The nineteenth century (The Library of America, 1996)
Contents of the book is contains newly researched biographical sketches of each poet and extensive notes. Throughout are favorite recitation pieces like"A visit from Saint Nicholas" and Casey At the Bat" and polular ballads, hymns, and songs like.